Is this back pain killing me? All‐cause and cardiovascular‐specific mortality in older Danish twins with spinal pain. (17th February 2017) - Fernandez, M.; Boyle, E.; Hartvigsen, J.; Ferreira, M.L.; Refshauge, K.M.; Maher, C.G.; Christensen, K.; Hopper, J.L.; Ferreira, P.H.
Abstract: Background: Few studies have examined the potentially reduced life expectancy associated with spinal pain (i.e. low back and neck pain) in an ageing population, particularly after controlling for familial factors, including genetics. Methods: We investigated whether spinal pain increased the rate of all‐cause and disease‐specific cardiovascular mortality in older Danish twins aged ≥70 years. Data from 4391 participants collected at baseline were linked with the Danish Cause of Death Registry with the study ending on 31 December 2014. Two crude and adjusted Cox proportional hazards regression analyses determined the rate of all‐cause and disease‐specific cardiovascular mortality by baseline spinal pain exposure; unpaired (total sample analysis) and twin pair (intra‐pair analysis). Analyses were also adjusted for confounders; baseline physical functional ability and depressive symptoms. Competing risk regression models determined the rate of cardiovascular mortality, adjusting for similar confounders and using the total sample only. Results: Spinal pain was associated with an increased rate of all‐cause mortality, hazard ratio (HR): 1.13 [95% confidence interval (CI): 1.06–1.21]. There was no association between spinal pain and cardiovascular disease mortality, sub‐distribution hazard ratio (SHR): 1.08 [95% CI 0.96–1.21]. After adjusting for confounders (physical functional ability and depressive symptoms), the association became non‐significant. All intra‐pair analyses were statistically non‐significant, although greater in magnitude for monozygotic twins. Conclusions: Older people reporting spinal pain have 13% increased risk of mortality per years lived but the connection is not causal. We found no association between spinal pain and cardiovascular‐specific mortality. The influence of shared familial factors is unlikely. Significance: Older people reporting spinal pain have 13% increased risk of mortality per year lived. However, this association is not likely to be causal, with the relevant confounders contributing to this relationship. Thus, pain in the spine may be part of a pattern of poor health, which increases mortality risk in the older population.